Leadership in Action : In Focus - Managing Conflict - New Challenges in a Changing World - Hannum, Kelly (Center for Creative Leadership, 2005)
In a progressively interdependent and diverse world, a major leadership challenge will increasingly be the need to lead groups of people with very different histories, perspectives, values, and cultures toward a common purpose.